Clinical and Biophysical Outcomes of Combining Microfocused Ultrasound with Visualization and Calcium Hydroxylapatite Filler for Facial Treatment - Martina Kerscher; Arti Tania Nurrisyanti; Christine Eiben-Nielson; Susanne Hartmann; Judith Lambert-Baumann (Adis, Springer Healthcare, 2018)
Abstract Introduction Combined cosmetic treatments are becoming increasingly popular. The objective of this clinical evaluation was to assess the long-term safety and efficacy of combining microfocused ultrasound with visualization (MFU-V) treatment with a calcium hydroxylapatite (CaHA) dermal filler to tighten skin at the submental region and contour the jawline. Methods Women with loss of contour and skin laxity in the lower face received MFU-V treatment. If subjects did not respond satisfactorily after 12 weeks, they received CaHA to the jawline. Evaluations-which were performed by blinded raters at baseline and after 12, 24, and 48 weeks-included live Global Aesthetic Improvement Scale (GAIS) ratings, Merz Aesthetic Scale (MAS) ratings, skin parameters, and tolerability. Results Of the 22 subjects, 9 received combined treatments. GAIS scores showed that subjects were much and very much improved (50% each) at 48 weeks. The MAS score was decreased by at least one point in 89% of subjects. Skin thickness was significantly improved after 24 weeks (p < 0.05) and remained above baseline after 48 weeks. Skin firmness was significantly improved after 48 weeks (p < 0.05). No unexpected adverse events were reported. Conclusion Combined MFU-V and CaHA treatments for laxity in the lower face did not alter skin barrier function, improved appearance, and slowed visible skin aging processes for at least 48 weeks. Funding Merz Pharmaceuticals GmbH.